Analisis Kualitas Oli Mesin TMO 10W-30 pada Innova Zenix Hybrid M20A-FKS Ditinjau dari Jarak Tempuh - Effendi, Ryan; Aini, Muhammad; Saksono, Puji (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Engine oil plays a crucial role in maintaining engine performance and longevity, especially in hybrid vehicles, which have a more complex operating cycle compared to conventional vehicles. This study was conducted to analyze the effect of mileage on the quality of TMO 10W-30 engine oil in the Toyota Innova Zenix Hybrid M20A-FKS. The results showed that the farther the vehicle traveled, the more the oil quality deteriorated, with viscosity decreasing from 9.77 cSt to 8.06 cSt at 10,000 km. Wear metal analysis revealed that Fe increased from <1 ppm to 11 ppm, Cu from 1 ppm to 22 ppm, and Al from 2 ppm to 8 ppm at 10,000 km